Online Platform Intermediary Liability under the Electronic Information and Transactions (ITE) Law, Freedom of Expression (FoE) Safeguards in Indonesia - Arief Fahmi Lubis (Eastasouth Institute, 2026)
The increasing reliance on online platforms as primary spaces for public communication has intensified legal debates on intermediary liability and freedom of expression in Indonesia. This study examines the legal construction of online platform intermediary liability under the Electronic Information and Transactions (ITE) Law and its implications for freedom of expression safeguards using a normative juridical approach. Through analysis of statutory provisions, implementing regulations, constitutional principles, and relevant legal doctrines, the study finds that the ITE Law adopts a conditional intermediary liability model that remains broadly formulated and lacks clear standards of responsibility. Such ambiguity encourages risk-averse compliance by online platforms and increases the likelihood of overblocking and chilling effects on lawful expression. The results further indicate that the delegation of content control to private platforms, combined with limited procedural safeguards and judicial oversight, poses challenges to the effective protection of freedom of expression. This article argues that clearer liability standards, explicit safe harbor mechanisms, and strengthened due process protections are necessary to ensure proportional regulation of online content while maintaining alignment with constitutional guarantees and international human rights norms.